Targeting Lipid—Ion Channel Interactions in Cardiovascular Disease - Hudgins, Emma C.; Bonar, Adam M.; Nguyen, Thanh; Fancher, Ibra S. (Frontiers in Cardiovascular Medicine, 2022)
General lipid-lowering strategies exhibit clinical benefit, however, adverse effects and low adherence of relevant pharmacotherapies warrants the investigation into distinct avenues for preventing dyslipidemia-induced cardiovascular disease. Ion channels play an important role in the maintenance of vascular tone, the impairment of which is a critical precursor to disease progression. Recent evidence suggests that the dysregulation of ion channel function in dyslipidemia is one of many contributors to the advancement of cardiovascular disease thus bringing to light a novel yet putative therapeutic avenue for preventing the progression of disease mechanisms. Increasing evidence suggests that lipid regulation of ion channels often occurs through direct binding of the lipid with the ion channel thereby creating a potential therapeutic target wherein preventing specific lipid-ion channel interactions, perhaps in combination with established lipid lowering therapies, may restore ion channel function and the proper control of vascular tone. Here we first detail specific examples of lipid-ion channel interactions that promote vascular dysfunction and highlight the benefits of preventing such interactions. We next discuss the putative therapeutic avenues, such as peptides, monoclonal antibodies, and aspects of nanomedicine that may be utilized to prevent pathological lipid-ion channel interactions. Finally, we discuss the experimental challenges with identifying lipid-ion channel interactions as well as the likely pitfalls with developing the aforementioned putative strategies.